‘ABV04’ A NEW BAJRA VARIETY SUITABLE TO THE TRIBAL AREAS OF ASR DISTRICT - A , SOWJANYA (The Journal of Research ANGRAU, 2026)
Frontline demonstrations on the pearl millet variety ABV-04 were conducted over two consecutive years (2023-24 and 2024-25) in the tribal regions of Alluri Sitarama Raju (ASR) district to evaluate its performance under rainfed upland conditions. A total of 20 demonstrations covering 8 hectares were carried out to compare the yield advantage of ABV-04 over the existing local farmer practice, i.e., Pittaganti variety. The results indicated that ABV-04 consistently outperformed local landraces, recording a pooled average grain yield of 1451.3 kg ha-1, compared to 979.9 kg ha-1 from the Pittaganti variety, with a yield advantage of 47.6%. In the first year, the variety showed a 57.7% higher yield, while in the second year, the yield advantage was 37.6%, despite climatic challenges such as reduced rainfall and delayed sowing.In addition, a gap analysis based on these frontline demonstrations was carried out to assess performance and identify yield-limiting factors. The average technology gap was 1176.3 kg ha-1, indicating constraints such as poor soil fertility, erratic rainfall, and low input usage. The extension gap averaged 471.4 kg ha-1, demonstrating the effectiveness of improved practices over traditional methods. The technology index was recorded at 42.0%, suggesting moderate feasibility under field conditions and highlighting the need for enhanced adoption support.